The Feasibility of Targeted Magnetic Iron Oxide Nanoagent for Noninvasive IgA Nephropathy Diagnosis - Wu, Yaoyao; Huang, Qiang; Wang, Junli; Dai, Yuhua; Xiao, Ming; Li, Yangyang; Zhang, Hongbo; Xiao, Wenbo (Frontiers in Bioengineering and Biotechnology, 2021)
IgA nephropathy is the most common glomerular disease in the world and has become a serious threat to human health. Accurate and non-invasive molecular imaging to detect and recognize the IgA nephropathy is critical for the subsequent timely treatment, otherwise it may progress to end-stage renal disease and lead to glomerular dysfunction. In this study, we have developed a sensitive, specific and biocompatible integrin αvβ3-targeted superparamagnetic Fe3O4 nanoparticles (NPs) for the noninvasive magnetic resonance imaging (MRI) of integrin αvβ3, which is overexpressed in glomerular mesangial region of IgA nephropathy. The rat model of IgA nephropathy was successfully established and verified by biochemical tests and histological staining. Meanwhile, the clinical 18F-AlF-NOTA-PRGD2 probe molecule was utilized to visualize and further confirmed the IgA nephropathy region in vivo via positron emission computed tomography. Subsequently, the Fe3O4 NPs were conjugated with arginine-glycine-aspartic acid (RGD) molecules (Fe3O4-RGD), and their integrin αvβ3-targeted T2 weighted imaging (T2WI) potential have been carefully evaluated. The Fe3O4-RGD demonstrated a great relaxation in vivo. The T2WI signal of renal layers in targeted group at 3 hours after intravenous injection of Fe3O4-RGD was distinctly lower than baseline, indicating MRI signal enhancement in established IgA nephropathy rat model. Moreover, the TEM characterization and Prussian blue staining confirmed the Fe3O4-RGD was located at region of glomerulus and tubular interstitium. Moreover, no obvious signal was detected in the untargeted Fe3O4 treated and control groups. Collectively, our results establish the possibility of Fe3O4-RGD that can be potentially serve as a feasible MRI agent for noninvasively diagnosis of IgA nephropathy